1990
DOI: 10.1111/j.1751-1097.1990.tb08667.x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Studies on the Antiinflammatory Drug Diclofenac

Abstract: Irradiation with UVA light of the anti-inflammatory drug diclofenac [2-(2,6-dichloroanilino)phenylacetic acid] in aqueous buffer or methanol solution leads to sequential loss of both chlorine substituents and ring closure to carbazole-1-acetic acid as the major product. Minor products result from substitution by the solvent. The photosensitizing properties of diclofenac and its major photoproduct were tested with singlet oxygen substrates and in the free radical polymerization of acrylamide. Although the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 29 publications
(29 reference statements)
9
50
2
Order By: Relevance
“…Degradation was accompanied by a significant decrease in pH because of the dehydrochlorination of DCF leading to the formation of hydrochloric acid and, after further degradation, other organic acids such as formic and oxalic acid. [40] In contrast to the rapid [41] A recent study also reported a high degradation rate for DCF on UV irradiation, emitted from a MP mercury lamp. [39] Another study, however, reported an insignificant degradation efficiency upon direct photolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation was accompanied by a significant decrease in pH because of the dehydrochlorination of DCF leading to the formation of hydrochloric acid and, after further degradation, other organic acids such as formic and oxalic acid. [40] In contrast to the rapid [41] A recent study also reported a high degradation rate for DCF on UV irradiation, emitted from a MP mercury lamp. [39] Another study, however, reported an insignificant degradation efficiency upon direct photolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of intermediates C1 and C2 were confirmed in both negative and positive ESI modes. These carbazole intermediates have also been identified as major products in a photolytic degradation of DCF in methanol [40] and have been linked to an increase in phototoxicity. [41] Decarboxylation of DCF led to the formation of C3, 2,6-dichloro-N-o-tolylbenzenamine (t R ¼ 6.8 min), [41] This compound, proposed as an intermediate in the transformation from C3 to C4, was undetectable, possibly because of its rapid oxidation under the conditions investigated.…”
Section: Photocatalytic Transformation Productsmentioning
confidence: 99%
“…This has been confirmed by photopatch tests studies [25], as well as by the in vivo mouse tail technique [26]. Photodegradation of DCF yields 1-(8-chlorocarbazolyl)acetic acid (ppDCF) as the major photoproduct [24,27] (Figure 1.18). For ppDCF, two transient species are observed by LFP (Figure 1.19).…”
Section: Phototoxicity Of Halogenated Nonsteroidal Antiinflammatory Dmentioning
confidence: 65%
“…[42][43][44][45] However, in spite of their wide use as antifungal agents, the photobehavior of these azole drugs has been scarcely investigated [46][47][48][49]. In this context, itraconazole has been selected here to investigate whether free radicals arising from a photodehalogenation process may be responsible for the observed in vivo photosensitivity responses [50]. As a matter of fact, the 2,4-dichlorophenyl moiety of 1 presents some photochemical similarities with the photolabile nonsteroidal antiinflammatory drugs carprofen or diclofenac (see introduction chapter).…”
Section: Itraconazole and Its Photoadverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation